Dampak Digitalisasi Dan Inovasi Produk Terhadap Peningkatan Penjualan Umkm Seblak Prasmanan Di Kampung Melayu Kraksaan - Junaedi, Deddy; Fitryningtyas, Cahya; Fatimah, Dian; Dwivo Monica Risqi Putri; Rosanti, Nur Mauliddyah; Wardani, Risma (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the impact of digitalization and product innovation on increasing sales of the Seblak Prasmanan MSME in Kampung Melayu Kraksaan. The digitalization discussed includes the use of social media, online delivery services, and various other digital platforms that support the promotion and sales process. Product innovation includes developing flavor variations, packaging design, and presentation that appeals to customers. The method applied in this study is descriptive quantitative with a Likert-scale questionnaire distributed to 70 respondents. The sample was taken using a purposive sampling technique, which prioritizes the criteria of active consumers. Data were analyzed using descriptive statistics using frequency and percentage tabulations to describe consumer views on the digitalization and product innovation implemented. The results of the study indicate that the majority of respondents strongly agreed that digital content can increase consumer interest, and the use of social media and delivery applications is very helpful in transactions. Respondents also stated that flavor variations and attractive packaging can increase purchasing interest and loyalty to the product. These findings indicate that the combination of digital technology utilization and creative product development can strengthen competitiveness and improve MSME sales performance.